2000
DOI: 10.4319/lo.2000.45.6.1368
|View full text |Cite
|
Sign up to set email alerts
|

Changes in a tidepool fish assemblage on two scales of environmental variation: Seasonal and El Niño Southern Oscillation

Abstract: Intertidal organisms are influenced by the tidal, daily, and seasonal environmental variability of their habitat. Interannual variability, although often less severe than shorter-scale variability, may also be important in structuring intertidal systems. This study compares the magnitude of changes in a rocky intertidal fish guild occurring on a seasonal scale with those occurring during an El Niño Southern Oscillation (ENSO). I examined tidepool fish assemblage structure and habitat use in two southern Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
4
39
0
Order By: Relevance
“…Godı´nez-Domı´nguez et al (2000) noted that after an El Nin˜o/La Nin˜a event the coastal fish fauna was also temporarily altered but returned to the pre-disturbance pattern in the next year. In a study of rocky intertidal fish, Davies (2000) reached a similar conclusion, with the return to pre-disturbance levels being attained soon after the end of the El Nin˜o event. Gibson (1967a) although in a very different context, noted that in the cold temperate waters of Britain, in some exceptionally cold winter periods, several individuals of Lipophrys pholis (a typical rocky intertidal resident species in west Europe) were found torpid or dying in the pools.…”
Section: General Patternsmentioning
confidence: 61%
“…Godı´nez-Domı´nguez et al (2000) noted that after an El Nin˜o/La Nin˜a event the coastal fish fauna was also temporarily altered but returned to the pre-disturbance pattern in the next year. In a study of rocky intertidal fish, Davies (2000) reached a similar conclusion, with the return to pre-disturbance levels being attained soon after the end of the El Nin˜o event. Gibson (1967a) although in a very different context, noted that in the cold temperate waters of Britain, in some exceptionally cold winter periods, several individuals of Lipophrys pholis (a typical rocky intertidal resident species in west Europe) were found torpid or dying in the pools.…”
Section: General Patternsmentioning
confidence: 61%
“…To evaluate the hypothesis of El Niño effects versus ''normal'' interannual variability, we compared recruitment rates between July 1997and May 1998-1998 versus those between July 1998and May 1999(1998-1999 and between July 1999and May 2000(1999-2000. The period was determined according to data from González et al (1998) and Blanco et al (2001) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is expected that El Niño would cause major and clearly detectable changes in patterns of recruitment of benthic and pelagic invertebrates and fish. Indeed, several studies have attributed increased or decreased recruitment of different species to El Niño (Paine 1986;Ebert et al 1994;Moreno et al 1998;Davis 2000). However, the strength of the evidence for El Niño effects on recruitment is limited by the temporal and spatial scope of the studies; most studies are short in duration and limited to one or a few sites.…”
mentioning
confidence: 99%
“…Migration was thought to be minimal because Clinocottus analis has strong homing tendencies (Williams 1957, Richkus 1978, Yoshiyama et al 1992, and because other studies of tidepool sculpins have reported little migration, even when accounting for emigration and immigration (Pfister 1996). Even if some migration occurred, low alongshore variability in population structure (indicated by the similarity in population structure between the 2 study sites [Davis 2000a]) suggests that neighboring populations were unlikely to serve as sources or sinks of particular size classes. Therefore, lack of emigration and immigration measurements probably did not produce much bias.…”
Section: Methodsmentioning
confidence: 99%
“…In such a case, the relative importance of recruitment versus post-recruitment processes could change over time depending on climate. C. analis population size is known to have declined during the 1997 to 1998 El Niño event (Davis 2000a). In the current study, we determined whether pre-recruitment or post-recruitment events were the sources of the ENSO variation in population size.…”
Section: Introductionmentioning
confidence: 99%